PENGARUH RADIUS POJOK TERHADAP KEKASARAN PERMUKAAN PADA PRODUKSI SILINDERIS AA-6061 MENGGUNAKAN PROSES BUBUT - Sudjatmiko, Sudjatmiko; Darto, Darto; Rusdijanto, Rusdijanto (INFO-TEKNIK, 2016)
Research machining with turning process, carried out in 6061 AA- workpiece material, using the HSS has a standard geometry. The problem is the corner radius (RCB), spindle rotation (n), the motion eat (f) and the cutting depth (a) constant to produce lathe AA-6061 with the desired surface and is capable of producing a high production capacity. The regression model can describe the relationship between the combination of cutting parameters and corner radius produces minimum surface roughness. Round spindle is a dominant effect on the surface roughness, followed by motion meal, corner radius (RCB). By using Response Surface Methodology (RSM), the alleged best regression model for surface roughness (SR) at 95% confidence level at 900 rpm spindle rotation, motion eat 115 mm / put and corner radius 1.25 mm is : 0,14x2x3. Results obtained by iterating the main influence on the conditions of rotation of 950 rpm, 90 mm motion eat / put and corner radius 1.50 mm produces the value of surface roughness( SR) 0,360 Âµm.